Sertoli cell–specific coxsackievirus and adenovirus receptor regulates cell adhesion and gene transcription via β‐catenin inactivation and Cdc42 activation. Issue 6 (20th March 2019) - Huang, Kun; Ru, Beibei; Zhang, Yang; Chan, Wai-Lung; Chow, Sheung-Ching; Zhang, Jiangwen; Lo, Clive; Lui, Wing-Yee
ABSTRACT: Blood‐testis barrier (BTB) and apical ectoplasmic specialization (ES) serve as structural supports for germ cell (GC) development. We demonstrated that the Sertoli cell (SC)‐specific coxsackievirus and adenovirus receptor (CXADR) knockout (SC‐CXADR −/− ), but not the GC‐specific knockout, impaired spermatogenesis. An increase in GC apoptosis and premature loss of elongated spermatids were observed in SC‐CXADR −/− testes. The BTB function was compromised in SC‐CXADR −/− testes with dysregulation of oocludin and zonula occludens‐1 expression at the basal compartment of the seminiferous epithelium. An integrated omics analyses confirmed that altered gene ontology terms identified in SC‐CXADR −/− testes are highly associated with spermatid development and differentiation, spermatogenesis, and sperm motility and are considered as unique testicular function terms. Leptin, Nasp, Tektin3, Larp 7, and acrosin, which are highly associated with male fertility, were found to be down‐regulated in SC‐CXADR −/− testes. Based on the data from the omics analyses, we employed the CXADR‐deficient SC model to further investigate the molecular mechanisms involved. We unraveled that SC‐CXADRs are required for β‐catenin inactivation and cell division cycle protein 42 (Cdc42) activation, resulting in maintaining the integrity and function of the BTB and apical ES as well as inhibiting gene transcription, such as the Myc gene, in the testes. We demonstrated for the first time that CXADR is an important mediator governing β‐catenin and Cdc42 signaling that is essential for spermatogenesis. The molecular mechanisms identified herein may provide new insights to unravel the novel functions and signaling cascades of CXADR in other key CXADR‐expressing tissues.—Huang, K., Ru, B., Zhang, Y., Chan, W.‐L., Chow, S.‐C., Zhang, J., Lo, C., Lui, W.‐Y. Sertoli cell‐specific coxsackievirus and adenovirus receptor regulates cell adhesion and gene transcription via β‐catenin inactivation and Cdc42 activation. FASEB J. 33, 7588–7602 (2019). www.fasebj.org